Strategic spending in voting competitions with social networks - Carlos Lever Guzmán (Banco de México, 2010)
This paper proposes a model of voting competitions (political campaigns and strategic lobbying) where voters are influenced by the opinion of their neighbors on a social network. In the unique pure strategy nash equilibrium, resources are targeted toward individuals with an influential position in the network. This finding contrasts with previous theories of strategic spending which predict that parties (or lobbies) should spend more on individuals who have a higher probability of being pivotal for the vote. The paper then tests the model using data on campaign contributions by interests groups in the US. House of Representatives. The estimations show that both network influence and pivotality are significant predictors of campaign contributions.
Keywords: D85; D72; 330; network games; strategic spending; Colonel Blotto games; counteractive lobbying; Bonacich centrality